´´La disortografía en el proceso de enseñanza-aprendizaje ´´. - Tasinchana Yugcha, Evelyn Mishell (2024)
Within the didactic process, the acquisition of spelling skills is considered a determining factor in one's formation. In this regard, the research aimed to identify the effect of dysorthographia on the teaching-learning process through documentary review. The methodology used was based on a qualitative approach, allowing for the collection of truthful information that described and understood how dysorthographia occurs in the teaching-learning process, which is bibliographical in nature as it aided in obtaining new knowledge. By applying the correlational method as a means to establish a relationship between the variables under study. The theoretical insights into dysorthographia are considered a specific learning problem that significantly affects the quality of spelling and, therefore, could hinder students from achieving the required learning outcomes. In conclusion, it is imperative to implement strategies to overcome these difficulties and ensure that students receive a quality education.